Experimental evaluation of a novel solar receiver for a micro gas-turbine based solar dish system in the KTH high-flux solar simulator. (15th September 2018) - Aichmayer, Lukas; Garrido, Jorge; Wang, Wujun; Laumert, Björn
Abstract: This work presents the experimental evaluation of a novel pressurized high-temperature solar air receiver for the integration into a micro gas-turbine solar dish system reaching an air outlet temperature of 800 °C. The experiments are conducted in the controlled environment of the KTH high-flux solar simulator with well-defined radiative boundary conditions. Special focus is placed on providing detailed information to enable the validation of numerical models. The solar receiver performance is evaluated for a range of operating points and monitored using multiple point measurements. The porous absorber front surface temperature is measured continuously as it is one of the most critical components for the receiver performance and model validation. Additionally, pyrometer line measurements of the absorber and glass window are taken for each operating point. The experiments highlight the feasibility of volumetric solar receivers for micro gas-turbine based solar dish systems and no major hurdles were found. A receiver efficiency of 84.8% was reached for an air outlet temperature of 749 °C. When using a lower mass flow, an air outlet temperature of 800 °C is achieved with a receiver efficiency of 69.3%. At the same time, all material temperatures remain below permissible limits and no deterioration of the porous absorber is found. Highlights: Pressurized volumetric solar air receiver tested in high-flux solar simulator. Receiver performance evaluated for multiple operating points. Receiver efficiency of 69.3% achieved for an air outlet temperature of 800 °C. Material temperatures remain below critical limits with no absorber deterioration. Test results highlight the feasibility of the concept and no major hurdles found.